19.10% Efficiency and 80.5% Fill Factor Layer‐by‐Layer Organic Solar Cells Realized by 4‐Bis(2‐Thienyl)Pyrrole‐2, 5‐Dione Based Polymer Additives for Inducing Vertical Segregation Morphology. Issue 6 (18th December 2022) - Zhou, Mingwei; Liao, Chentong; Duan, Yuwei; Xu, Xiaopeng; Yu, Liyang; Li, Ruipeng; Peng, Qiang
Abstract: The morphology plays a key role in determining the charge generation and collection process, thus impacting the performances of organic solar cells (OSCs). The limited selection pool of additives to optimize the morphology of OSCs, especially for the emerging layer‐by‐layer (LbL) OSCs, impeding the improvements of photovoltaic performances. Herein, a new method of using conjugated polymers as the additives to optimize the morphology for improving the photovoltaic performances of LbL‐OSCs is reported. Four polymers of PH, PS, PF, and PCl are developed with different side chains. These polymers exhibit poor performances as donor materials and additives in the BHJ devices, due to the unsuitable energy level alignment and unfavorable molecular interactions. By contrast, they can be served as efficient additives to optimize the PM6 fibril matrix for facilitating the penetration of BTP‐eC9 and forming an intertwined D/A bicontinuous network with a vertical segregation. Such morphology is optimized by side chain engineering, which enables the progressive improvement of the charge separation and collection. As a result, adding a small amount of PCl as the additive, the optimized morphology contributes to a champion PCE of 19.10% with a high FF of 80.5%. Abstract : A series of conjugated polymers by side chain engineering and used as additive, which enable a record power conversion efficiency of 19.10% and decent high FF of 80.5% in layer‐by‐layer processed organic solar cells.